A diffuse-interface lattice Boltzmann method for fluid–particle interaction problems. (30th January 2022) - Liu, Jiao; Huang, Changsheng; Chai, Zhenhua; Shi, Baochang
Abstract: In this paper, a diffuse-interface lattice Boltzmann method (DI-LBM) is developed for fluid–particle interaction problems. In this method, the sharp interface between the fluid and solid is replaced by a thin but nonzero thickness transition region named diffuse interface, where the physical variables change continuously. In order to describe the diffuse interface, we introduce a smooth function, which is similar to the order parameter in the phase-field model or the volume fraction of solid phase in the partially saturated lattice Boltzmann method (PS-LBM). In addition, to depict the fluid–particle interaction more accurately, a modified discrete force term is also proposed and included in the evolution equation of the DI-LBM. Some classical problems are used to test the DI-LBM, and the results are in good agreement with some available theoretical and numerical data. Finally, it is also found that the DI-LBM is more efficient and accurate than the PS-LBM with the superposition model. Highlights: A diffuse-interface lattice Boltzmann method (DI-LBM) for fluid–particle interaction problems is proposed. The method is effective and accurate in the study of the fluid–particle interaction problems. A detailed Chapman–Enskog analysis of the DI-LBM is performed.